Фотометрические и спектральные исследования группы галактических звезд Вольфа-Райе. I. WN последовательность - Кондратьева, Л. Н.; Рева, И. В.; Денисюк, Э. К.; Шомшекова, С. А.; Айманова, Г. К. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Фотометрические и спектральные наблюдения 11-ти звезд Вольфа-Райе WN последовательности выполнялись в АФИФ в 2021-2022гг. На основе проведенных наблюдений получены оценки блеска объектов в фильтрах BVRc и абсолютные потоки излучения в эмиссионных линиях. Изменения блеска в пределах 0m.1 - 0m.15 зарегистрированы в звездах WR 1, WR 120, WR 151, WR 152. Изменения эмиссионных потоков обнаружены в спектрах нескольких объектов: WR 120, WR 128, WR 145. Photometric and spectral observations of 11 W-R stars were carried out at the FAI in 2021-2022. The studied group included representatives of the WN, WC, and WO sequences. Based on the observations estimates of the brightness of objects in the B V Rc filters and absolute fluxes of radiation in the emission lines were obtained. Changes in brightness within 0m.1 - 0m.15 were detected in the stars WR 1, WR 120, WR 151, and WR 152. Changes in the emission fluxes were detected in the spectra of several objects: WR 120, WR 128, and WR 145.
Keywords: Астрофизика